Diffuse PTH expression in parathyroid tumors argues against important functional tumor subclones. Issue 5 (May 2016) - Haglund, Felix; Juhlin, C Christofer; Kiss, Nimrod B; Larsson, Catharina; Nilsson, Inga-Lena; Höög, Anders
Abstract: Objective: Primary hyperparathyroidism is usually characterized by a monoclonal parathyroid tumor secreting excess parathyroid hormone (PTH). The main regulator of PTH secretion is calcium and the calcium–PTH set point is shifted in parathyroid tumor cells. We sought to investigate the relationship between tumor PTH and PTH mRNA expression and clinical presentation as well as the regulatory factors including phosphate, vitamin D, and fibroblast growth factor 23. Design: A total of 154 parathyroid tumors were analyzed by PTH immunohistochemistry and chromogenic in situ hybridization of PTH mRNA. A subset of samples ( n = 34) was analyzed using quantitative real-time PCR. Results: Low tumor PTH mRNA level was significantly associated with low tumor PTH immunoreactivity ( P = 0.026), but the two did not correlate with regard to histological distribution within individual tumors. Tumors displaying reduced PTH mRNA levels as compared with normal rim were significantly larger ( P = 0.013) and showed higher expression of the calcium-s ensing receptor ( CASR ) ( P = 0.046). Weaker tumor PTH mRNA level was significantly associated with higher concentration of circulating 25-hydroxyvitamin D ( P = 0.005). No significant correlation was seen between PTH immunoreactivity and patient biochemistry. Tumor weight was strongly associated with circulatory concentrations of calcium and PTH. Conclusions: No areas with apparently higher PTH expression were identified, perhaps suggesting that hyper functioning parathyroid tumor subclones should be rare. Circulating 25-hydroxyvitamin D levels may influence tumor PTH expression in vivo . If PTH immunoreactivity reflects the tumor calcium–PTH set point, our data imply that the main determinant of disease severity should be tumor weight.